Identificaciòn de células epiteliales vaginales dominantes en ovulación para mejorar los ìndices reproductivos en hembras bovinos - Calderón Castillo, Jhon Darwin (2016)
VIII. SUMARY In the present investigating work came true the identification of epithelial vaginal dominant present cells in ovulation and in the different phases intervening estrales the method of vaginal cytology exfoliativa, accompanied of the rectal palpation, that way relating them 7.5 of the road to the follicular size in 17 bovine females of mixed racial ancestry of the Technical University of Babahoyo located in the km Babahoyo Montalvo of the Province it is whose geographic coordinates of The Rivers, to 7,5 msnm's height of 79 32`de length west and 01 49`de southern latitude. The zone presents tropical climate characterized by a temperature annual mean of 25 C, with relative humidity of 76 % and precipitation of 2791,4 mm year. The principal objective in this work was to get better index them reproductive in bovine females. Exfoliativa and rectal palpation during the four phases of cycle utilized the methods of vaginal cytology themselves estral and in four consecutive jealousy (84 days). The obtaining of signs and rectal palpaciones to the bovine females accomplished them every day to the 07:00 hours. In order to determine results himself I make the descriptive statistics not parametric. 88.24 % of the cows of mixed racial ancestry of the cattle raising of Babahoyo's Technical University present a reproductive efficient capability besides in estrus according to the results the presence of epithelial vaginal overdue cells and cornificadas attain an average ( 23.84 and 62.61 % ) respectively in relation to the epithelial vaginal cells parabasales ( 4.13 % ), premature ( 19.60 % ), and medians (28.10 %) existing a descriptive relation between the dominant presence of epithelial vaginal cells cornificadas (40.11 %) and the follicular big size (19.22 %) is an indicator of estrus. The determination of intervening estrus the vaginal cytology exfoliativa in bovine females together with the rectal palpation in conclusion proves to be efficient and of low cost.